Assessing the taxonomic identity and distribution of endemic and critically endangered Cynometra cebuensis F. Seid. (Fabaceae) in Cebu Island, Philippines - EDGARDO P. LILLO; ARCHIEBALD B. MALAKI; STEVE MICHAEL T. ALCAZAR; MARIA LEVY M. CHAVEZ; DEMETRIO M. CAÑARIJO III; ERWIN M. PANTINOPLE; BERNARDO R. REDOBLADO; MARVIN A. MARGATE; JOHN LOU DIAZ; KRISTEL MAY C. FLORES; JESSA MARIE P. LILLO; CHRISTINE FAYE O. GONZAGA; RAAMAH ROSALES; ARNALDO ALMIRANTE; CHRISTINE JOY TOMOL (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Lillo EP, Malaki AB, Alcazar SMT, Chavez MLM, Cañarijo III DM, Pantinople EM, Redoblado BR, Margate MA, Diaz JL, Flores KMC, Lillo JMP, Gonzaga CFO, Rosales R, Almirante A, Tomol CJ. 2023. Assessing the taxonomic identity and distribution of endemic and critically endangered Cynometra cebuensis F. Seid. (Fabaceae) in Cebu Island, Philippines. Biodiversitas 24: 4854-4861. Cynometra cebuensis F. Seid. is a newly discovered species and considered endemic to Cebu Island, Philippines. Yet, it faces extinction threats, making it a critically endangered species. Information on the taxonomical certainty and geographical ranges is important to facilitate its protection and conservation. Therefore, this study focuses on the identification and distribution of C. cebuensis in Cebu Island, Philippines. Field surveys were conducted across various Key Biodiversity Areas and the Cebu Central Protected Landscape, specifically the Tabunan forest, to ascertain the distribution of these species. The Leaf Architectural Working Group Manual was employed to meticulously describe leaf characteristics, supplemented by information from published literature. Contrary to previous assumptions that C. cebuensis F. Seid. exclusively inhabited the Tabunan forest within Cebu Central Protected Landscape, this study reveals its presence in multiple areas outside Tabunan. Notably, C. cebuensis F. Seid. displays several distinct characteristics that differentiate it from other congeners, encompassing leaf structure, shape, fruit dimensions, growth patterns, and a unique identification key. Given its confinement to Cebu Island, C. cebuensis F. Seid. is acknowledged as an endemic species. Accurate identification of this species assumes pivotal importance in steering effective conservation endeavors. However, its distribution is observed to be confined to a few remaining forested patches. This emphasizes the urgency of safeguarding the Key Biodiversity Areas within Cebu Island, Philippines, where the exclusive presence of C. cebuensis F. Seid. has been ascertained.